GATHERING DATA AND WRITING LIBRARY ANNUAL REPORT: AN OVERVIEW (2016)
All university libraries, in order to support the university's curriculum; to support the research of the university faculty and students; and for planning purposes, writes an annual report. This annual report gives details about the activities of the library in terms of, achievements (Success Stories), key statistics to back up claims, staff matters, challenges, among others, during the year under review. It is amazing that in practice this library culture is being eroded in new generation librarianship due to the fact that in the library school this practice is neither taught nor laid emphasis upon again while many professionals do not know how to gather the necessary data and write useful library report. Upon this backdrop this paper presented detail data gathering method for useful annual report writing. 4 The study adopted a narrative methodology while in the analysis of the study the data to be generated for library report was described to be the core functions of the university. The university library (i.e. Kenneth Dike Library, University of Ibadan), over years, has been living up to expectation in this direction of generating these data. The data is to be used to write reports expected to highlight the activities of the entire university library system that occurred during the year under review. This strategic responsibility is a germane one for the university library in academic community, therefore, cannot be over emphasized. Some of the data were highlighted as Access and Collection Development (ACD); Community Engagement; Information Services regardless of their geographical locations; and strategic Academic Role. Suggested stages involved generally in report ivriting information flow includes: Set sectional/units' goals for the year and give brief description of how to achieve it; Make presentation at divisional/sectional/unit level, as the case may be, to review the set goals/objectives before commencing implementation; Commence implementation and meet, fortnightly/ monthly to present progress report, backed up with statistics; Hold quarterly meetings to present quarterly report of activities; At the end of the fourth quarter (i.e., July to September), collate the reports of the four (4) quarters and generate your annual report based on the statistics you have at your disposal; Call library management meeting for final presentation ofsections/units' reports by the divisional heads; The final collation of the reports is done by the administrative officer of the library who is the secretary at the library management meeting; The university librarian writes foreword and a covering memo attached to the report for onward submission to the university management. While the suggested outline for writing library annual reports includes: Introduction; State the major activities being carried out in the sections/units; Staff Affairs; State the set goals for the year as well as how to achieve it; Data presentation and analysis on quarterly basis and ensure that success stories are highlighted; Present challenges which are militating against the success of sections and units; Summary and recommendations. Annual report is an important document for research, planning and policy formulation for library and the university.